2005
DOI: 10.1037/0894-4105.19.4.520
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in preclinical Alzheimer's disease: A meta-analysis.

Abstract: To determine the size of the impairment across different cognitive domains in preclinical Alzheimer's disease (AD), a meta-analysis based on 47 studies involving 9,097 controls and 1,207 preclinical AD cases was conducted. There were marked preclinical deficits in global cognitive ability, episodic memory, perceptual speed, and executive functioning; somewhat smaller deficits in verbal ability, visuospatial skill, and attention; and no preclinical impairment in primary memory. Younger age (Ͻ 75 years) and shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
478
7
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(552 citation statements)
references
References 109 publications
60
478
7
7
Order By: Relevance
“…The posterior localisation of the correlation on the EEG agrees with the cerebral area responsible for the cognitive speed measured by AQT [58]. Meta-analysis of cognitive decline in AD has further presented perceptual speed as one of the first cognitive entity affected [2]. Overall, cognitive decline becomes visible later than biomarkers in AD development [15].…”
Section: Discussionmentioning
confidence: 65%
“…The posterior localisation of the correlation on the EEG agrees with the cerebral area responsible for the cognitive speed measured by AQT [58]. Meta-analysis of cognitive decline in AD has further presented perceptual speed as one of the first cognitive entity affected [2]. Overall, cognitive decline becomes visible later than biomarkers in AD development [15].…”
Section: Discussionmentioning
confidence: 65%
“…The hypothesis of an executive impairment in the preclinical phase of AD is consistent with other studies. Reviews and metaanalyses (Bäckman et al, 2004;Bäckman et al, 2005) of both longitudinal population-based samples and studies on subjects with MCI have evidenced that together with episodic memory deficits, changes in executive functioning and perceptual speed were present in the very early phases. In the same vein, the PAQUID cohort (Amieva et al, 2005) has shown that multiple cognitive functions are affected in the premorbid phase of the AD among which executive …”
Section: Discussionmentioning
confidence: 99%
“…In a detailed review of the literature concerned with preclinical AD, Backman et al (2004Backman et al ( , 2005, for example, argued that the cognitive decline in the 2 or 3 years preceding a nonnormal diagnosis is largely nonspecific. However, they reviewed methodologically diverse studies, many of which did not follow the design guidelines that characterized our study.…”
Section: Discussionmentioning
confidence: 99%
“…At the other extreme, impairment in preclinical AD patients may exhibit a relatively nonspecific pattern involving similar deficits on the entire battery of neuropsychological tests (cf. Backman et al, 2005).…”
Section: Correlating Neuropsychological Test Performance Withmentioning
confidence: 99%